Effects Of Nitrogen and Different Rates of Pendimethalin with Bispyribac-Sodium on Direct-Seeded Aus Rice (Bangladesh Agronomy Journal, 2025)
The study was conducted at Sher-e-Bangla Agricultural University in Bangladesh, aiming to investigate the effects of nitrogen rates and herbicides on the competitiveness and yield parameters of dry direct-seeded rice (DSR) from March to July 2022. There were two factors in the experiment: nitrogen rates of 60 kg ha−1 (N60) and 80 kg ha−1 (N80), and the application of pre-emergent herbicide pendimethalin followed by post-emergent herbicide bispyribac-sodium. The herbicide treatments included: no weeding (H0), pendimethalin at 1000 g a.i. ha−1 (H1), bispyribac-sodium at 25 g a.i ha⁻1 (H2), pendimethalin at 500 g a.i. ha−1 combined with bispyribac-sodium at 15 g a.i. ha⁻1 (H3), pendimethalin at 1000 g a.i. combined with bispyribac-sodium at 30 g a.i. ha−1 (H4), and pendimethalin at 1500 g a.i. ha−1 combined with bispyribac-sodium at 45 g a.i. ha−1 (H5). The split-plot design consisted of 12 treatment combinations and 3 replications, with main plots for nitrogen rates and sub-plots for herbicidal treatments using rice var. BRRI dhan98. The result showed that the highest tiller number hill−1 was recorded for 80 kg ha−1 combined with pendimethalin 1000 g a.i. ha−1 + bispyribac-sodium 30 g a.i. ha−1 at 30, 45, 60, and 75 DAS, respectively. The study also exhibits the impact of nitrogen rates and herbicides on the dry weight of plants in BRRI dhan98 under the DSR system. Nitrogen rates did not significantly affect the dry weights of plants at 15, 30, and 45 days after sowing (DAS). However, the nitrogen rate of 80 kg N ha−1 resulted in the highest dry weight at 60 and 75 DAS. The study also found that the biological yield and harvest index of var. BRRI dhan98 were better (9.41 and 47.74, respectively) in 80 kg ha−1 combined with pendimethalin 1000 g a.i. ha−1 + bispyribac-sodium 30 g a.i. ha−1.Bangladesh Agron. J. 2024, 27(2): 61-69